2005
DOI: 10.1111/j.1365-2583.2004.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle profiles of EcR, USP, HR3 and B cyclin mRNAs associated to 20E‐induced G2 arrest of Plodia interpunctella imaginal wing cells

Abstract: Using the IAL-PID2 cell line established from pupally committed imaginal wing discs of Plodia interpunctella , we have investigated the dynamics of cellular and molecular events involved in the G2/M arrest. We have first cloned a cDNA sequence named PIUSP-2 that likely encodes a homologue of the Ultraspiracle-2 isoform of Manduca sexta . When the IAL-PID2 cells were exposed to a 8 h 20E treatment applied at different times of the cell cycle, an optimal period of sensitivity of cells to 20E, in inducing G2 arre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…This is accompanied by an arrest either at G2 [95,97,98] or at G1/S [99]. Periodic expression of EcR and Usp during the cell cycle and their impact on regulation of cell proliferation was reported recently [100][101][102]. EcR, but not Usp, reduces cyclin D1 expression.…”
Section: Ecdysteroids and Cell Cyclementioning
confidence: 99%
“…This is accompanied by an arrest either at G2 [95,97,98] or at G1/S [99]. Periodic expression of EcR and Usp during the cell cycle and their impact on regulation of cell proliferation was reported recently [100][101][102]. EcR, but not Usp, reduces cyclin D1 expression.…”
Section: Ecdysteroids and Cell Cyclementioning
confidence: 99%
“…In Plodia interpunctella, Siaussat et al (2008) report that EcR, Usp, and HR3 control the proliferation of imaginal discs by expression of cyclin B. A peridoc expression of EcR and Usp during the cell cycle was already reported by Siaussat et al (2005) in a Plodia interpunctella cell line.…”
Section: Ecr But Not Usp Concentration Varies During Cell Cyclementioning
confidence: 87%
“…Periodic expression of EcR and Usp during the cell cycle of insect cells was demonstrated by Siaussat et al (2005) in the lepidopteran cell line (Plodia interpuctella) with high levels of EcR and Usp at S/G2 transition (Debernard et al, 2001). The impact of EcR and Usp on the regulation of cell proliferation was shown recently (Siaussat et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, PiHR3 is a member of a steroid hormone receptor superfamily and clearly assigned to the HR3 subfamily. In the IAL-PID2 cell line, it has been reported that the 20E-induced G2/M arrest was associated with a large increase in the expression level of the PiEcR-B1, PiHR3 and PiUSP-2 (Mottier et al, 2004;Siaussat et al, 2005). To identify the molecular actors involved in the 20E signalling pathway responsible for G2/M arrest, we inhibited the 20E inducibility of EcR-B1, USP-2, HR3 by RNAi and then monitored the effects of each knockdown on the induction level of this cellular response.…”
Section: Isolation and Characterization Of P Interpunctella Hr3 Mrnamentioning
confidence: 99%